Variation in Yield, Free Proline Content and Cation Accumulation of Lemongrass (Cymbopogon flexousus) Varieties Grown in Sodic Soils - Prasad, Arun; Lal, R K; Chand, Sukhmal; Kumari, Raj (Annals of Arid Zone, 2016)
The variations in yield, free proline content and cation accumulation in five varieties of lemongrass (Pragati, Praman, CKP-25,Cauvery and Nima) in sodic soils of ESP (exchangeable sodium percentage) 18.0 and 36.0 were studied in a pot experiment. Irrespective of the soil sodicity level, all the varieties of lemongrass differed significantly in their herb and oil yield, free proline content and cation accumulation. The herb and oil yield of lemongrass significantly decreased with an increase in soil ESP from 18.0 to 36.0, however,. the extent of decrease in yield was lower for the varieties PramanÂ· and Nima and higher for the varieties Pragati and CKP-25. The total citral content in the essential oil was highest for the variety Nima and lowest in CKP-25. The free proline content was significantly higher in shoot tissues of lemongrass grown in the sodic soil of ESP 18.0 than in the sodic soils of ESP 36.0. The concentration of Na in shoot and root tissues of lemongrass increased and that of K and Ca decreased with an increase in the soil ESP. The concentrations of Na, K, and Ca were relatively higher in the shoot than in the root tissues of lemongrass. The relatively lower accumulation of Na and the capacity to maintain higher K/Na and Ca/Na ratios in shoot tissues of varieties Praman and Nima at high soil ESP showed their higher tolerance of soil sodicity as compared to varieties Pragati, CKP-25 and Cauvery. Key words: Lemongrass, herb and oil yield, soil exchangeable sodium percentage, cation accumulation, free proline content